ULTRAMICROSCOPIC RESEARCH OF WHITE RATS’ THYMUS AT EXPERIMENTAL IMMUNOSTIMULATION - Bobrysheva, I.V. (World of Medicine and Biology, 2013)
The features of ultramicroscopic structure of the thymus of white male rats of reproductive age at experimental immune stimulation are studied. It was established that the thymus of rats is characterized by a high degree of reactivity in response to the introduction of immunomodulator imunofan, which is manifested in increasing of lymphocytopoiesis due to increased mitotic activity of thymocytes of subcapsular and cortical regions of thymic lobules; proliferation and increased functional activity of epithelioreticular cells; increase of phagocytic activity of the thymus. The most pronounced changes in the ultrastructure of the thymus observed at 7 days after drug administration. The increased reactivity of the thymus is maintained for 30 days of observation.
Keywords: rats; thymus; experimental immunostimulation